Political Development in Nepal: A Perspective of Participation and Inclusion - Lamsal, Chakrapani (Curriculum Development Journal, 2020)
The political development in Nepal is analyzed from the angle of interpretive philosophy and the Inclusive approach. Nepal’s practice of inclusive democracy and federal governance is taken into consideration and diverse representation in the constitutional assembly and existing both the houses of parliament is historical achievement. My findings are that inclusive democracy is a suitable form of governance for Nepal where the population is heterogeneous in terms of caste and ethnicity. Delivery of equitable justice and inclusion of marginalized lower-income people is a major challenge for the success of the newly adopted political system. Political development shifts from the nation-state to state-nation, mono-culture to multicultural, unitary to federal, exclusionary to inclusive, absolutism to secularism, monarch to republican, parliamentary to inclusive democracy and parochial to the participatory system.